A biogeochemical model of mineral-based ocean alkalinity enhancement: impacts on the biological pump and ocean carbon uptake. (1st April 2023) - Fakhraee, Mojtaba; Li, Zijian; Planavsky, Noah J; Reinhard, Christopher T
Abstract: Minimizing anthropogenic climate disruption in the coming century will likely require carbon dioxide removal (CDR) from Earth's atmosphere in addition to deep and rapid cuts to greenhouse gas emissions. Ocean alkalinity enhancement—the modification of surface ocean chemistry to drive marine uptake of atmospheric CO2 —is seen as a potentially significant component of ocean-based CDR portfolios. However, there has been limited mechanistic exploration of the large-scale CDR potential of mineral-based ocean alkalinity enhancement, potential bottlenecks in alkalinity release, and the biophysical impacts of alkaline mineral feedstocks on marine ecology and the marine biological carbon pump. Here we a series of biogeochemical models to evaluate the gross CDR potential and environmental impacts of ocean alkalinity enhancement using solid mineral feedstocks. We find that natural alkalinity sources—basalt and olivine—lead to very low CDR efficiency while strongly perturbing marine food quality and fecal pellet production by marine zooplankton. Artificial alkalinity sources—the synthetic metal oxides MgO and CaO—are potentially capable of significant CDR with reduced environmental impact, but their deployment at scale faces major challenges associated with substrate limitation and process CO2 emissions during feedstock production. Taken together, our results highlight distinct challenges for ocean alkalinity enhancement as a CDR strategy and indicate that mineral-based ocean alkalinity enhancement should be pursued with caution.